The Case of the United States before the Tribunal of Arbitration to convene at Paris under the provisions of the treaty between the United States of America and Great Britain, concluded February 29, 1892 [electronic resource] : including the reports of the Bering Sea Commission. - Bering Sea Tribunal of Arbitration.; Bering Sea Commission.; United States. (Washington : G.P.O., 1892)
At head of title: Fur-seal arbitration. Includes indexes. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44